Pengaruh Kontrol Diri dan Lingkungan Sosial Terhadap Perilaku Pengelolaan Keuangan Pada Mahasiswa Universitas Negeri Padang - Nadya Annisa; Elvi Rahmi (Jurnal Ecogen, 2025)
This study aims to find out how self-control and the social environment affect how people manage their money of students at Universitas Negeri Padang (UNP). The study used a quantitative, causal, associative approach. The population used in this study was 63,752 active UNP students. The study used a method called cluster sampling, and the total number of participants was 199. Data collection used a questionnaire via Google Forms with a Likert scale. All instruments used have passed validity and reliability tests. The data analysis technique in this study employed descriptive and inductive analysis. The study used a method called multiple linear regression for analysis, which passed the prerequisite tests of normality, heteroscedasticity, and multicollinearity using SPSS Version 31.00. The researchers used f-tests, t-tests, and the coefficient of determination to check their ideas. The findings show that 1) having self-control helps students manage their money better; 2) the social environment also helps students manage their money better; and 3) both self-control and the social environment together have a strong influence on how students handle their finances.